Ternary blend organic bulk heterojunction photovoltaics based on incorporation of low bandgap materials - Ling, Jin (2011)
Bulk heterojunction (BHJ) organic photovoltaic (OPV) cell based on poly (3-hexylthiophene):[6, 6]-phenyl-C60-butyric acid methyl ester (P3HT:[C61]-PCBM) (P3HT:PCBM) is a promising binary materials blend system which has attracted extensive attention. However, the limited absorption spectrum of P3HT and the small energy difference between the highest occupied molecular orbital (HOMO) level of P3HT and the lowest unoccupied molecular orbital (LUMO) level of PCBM hinder the further enhancement of P3HT:PCBM BHJ OPV device performance. Ternary blend systems via incorporation of extra electron donor additives into the P3HT:PCBM binary blend, have the potential to overcome these restrictions. This project investigated two ternary blend systems based on incorporation of low bandgap polymer poly[[9-(1-octylnonyl)-9H-carbazole-2,7-diyl]-2,5-thiophenediyl-2,1,3-benzothiadiazole-4,7-diyl-2,5-thiophenediyl] (PCDTBT), and small molecule BDT-DPP-BDT (DPP) respectively. It was found that, both ternary blend systems succeeded in increasing the non-annealed device power conversion efficiency (PCE) due to broadened absorption spectrum and larger open circuit voltage (VOC). However, after thermal annealing, the PCE of P3HT:PCPDTDT:PCBM ternary blend system increased (from 2.14% to 2.84%) while the PCE of P3HT:DPP:PCBM ternary blend system decreased (from 3.27% to 2.37%). Atomic force microscopy (AFM) characterization revealed severe morphology perturbations in photovoltaic active layers of annealed device for both ternary systems. Morphology improvement via addition of solvent addictives and change of active layer solvent were attempted, however, both failed.